Sistem Penjadwalan Sidang Tugas Akhir menggunakan Algoritma Genetika - Susetyo Bagas Bhaskoro; Berlian Bayu Aji; Siti Aminah (P3M Politeknik Negeri Indramayu, 2021)
Objective this research is to automatically schedule student final assignments using genetic algorithms in the Automation Engineering Technology Study Program of the Manufacturing Polytechnic in Bandung. Genetic Algorithm (GA) is a heuristic method or a method of finding optimal values using the principles of evolution. GA is used as a solution search algorithm in this research. The solution was implemented into a program that can create a schedule automatically based on the limitations set by program users. Scheduling parameters that are focused on in this study are duplication or clash issues and category suitability between the final project and examiners. Based on these parameters the program can produce the optimal schedule with varying success rates depending on the ratio between the number of trial examiners and the number of examiners needed at one time, where a ratio above 2: 1 result in success above 90% for duplication cases, and the ratio is above 1.5: 1 for category conformance cases.